Prevalence of physical activity behaviour in older people: Findings from the Dynamic Analyses to Optimise Ageing (DYNOPTA) project and Australian national survey data. (17th October 2012) - Sims, Jane; Birrell, Carole L; Hunt, Susan; Browning, Colette; Burns, Richard A; Mitchell, Paul
<x xml:space="preserve">Abstract</x> Aim Many older people lead sedentary lives. National Health Survey physical activity prevalence data provide limited coverage of the 'old old' (≥75 years). Method The Dynamic Analyses to Optimise Ageing (DYNOPTA) project's dataset provided physical activity data for 13 420 participants. Physical activity (walking, moderate‐ and vigorous‐intensity activities in the previous week) was measured. Data were weighted and prevalence was calculated. Results The frequency of walking in DYNOPTA was similar to that in the national sample. Walking remained relatively stable until a decline among persons aged 80 years and over; moderate and vigorous activity declined in all but a minority of persons aged 70 years and over. Although DYNOPTA participants reported more physical activity than those in the contemporary national survey, the rates of sedentary behaviour were high. Conclusion We require more information about the 'oldest old' (85+ years). There is great scope for increasing physical activity, even walking, among older people.